An evaluation on components of experience based factory model in requirement engineering process: a preliminary study - Hanafiah, Mastura; Abdullah, Rusli (IEEE (IEEE Xplore), 2014)
xperience based factory and knowledge management are distinguished concepts in managing organizational knowledge and experiences. In software development, requirement engineering is a very crucial process; in addition, it is knowledge-intensive, repetitive and time-consuming activity. Knowledge and experiences in requirement engineering should be managed systematically and efficiently for sharing and reuse purposes to avoid any software pitfalls and to improve the software development as a whole. A model, namely Requirement Engineering for Experience Based Factory Model (RE-EBF-Model), has been proposed to manage requirement knowledge to maximize the benefit of knowledge sharing among the community of practice. This study takes a step further to elaborate the components dealing with requirement engineering processes. The preliminary evaluation of these components has been conducted with a pilot survey to pre-test the questionnaire and corroborate its validity and reliability. Findings show satisfactory result on the correlation between practitioners and the perceived RE sub-components, but further analysis highlights some problematic questions; therefore, the affected questions are revised and improved.